Equilibrium states of humid catchments satisfying both energy and mass conservations - Sanghyun Yoo; Kwanghun Choi; Kyungrock Paik (Geoscience Letters)
Abstract Natural catchments are supposed to obey both energy and mass conservations. As two conservation principles are related through evapotranspiration, the ideal energy partitioning at the equilibrium state also determines the mass partitioning. A fundamental question is how the incoming energy (solar radiation) and mass (precipitation) are distributed at the balancing state. We hypothesize that received energy and mass are distributed following the principle of maximum entropy production (MEP). Further, the resultant balancing state is anticipated to vary with environmental and physiographical settings, and vegetation phenology. This idea was thoroughly investigated, taking 14 humid catchments located over South Korea and Kyushu, Japan, covering wide ranges of precipitation, evapotranspiration, and temperature. Annual evapotranspiration estimated following the MEP principle indeed well agrees with evapotranspiration from global products, for every catchment. Annual Bowen ratio is found nearly invariant over years for a catchment, reflecting the phenological, physical, and physiographical characteristics of a humid catchment. The ratio exhibits the systematic variation following the climatic gradient of the region. In mass partitioning, clear 1:1 relationship between annual runoff Q and precipitation P, offset by the base loss L o which equals to the mean annual loss, was found. This relationship is restated as the one-to-one relationship between two dimensionless measures as Q/L o = P/L o − 1. The threshold of L o forms another characteristic constant of a catchment, and is associated with the mean annual Bowen ratio of the catchment.